SUPERVISI PEMBELAJARAN ERA 4.0 DENGAN MODEL LESSON STUDY UNTUK MENINGKATKAN DOUBLE PROFESIONALISME - Dra. Nur Habibah, M.Ag (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2021)
This Best Practice report aims to find out the double increase in professionalism of teachers in the Lumajang regency and the supervisors themselves in providing assistance in the 2019/2020 school year. This report involves 2 target schools using the supervision of learning era 4.0 with the lesson study model. Supervision of learning era 4.0 model Lesson Study is a joint activity carried out by the teacher and supervisor in supervising learning activities to make preparations for teaching together, then the model teacher teaches in accordance with the plans that have been prepared while the supervisor observes the learning. The results of this reflection are used as material for consideration to plan and carry out further learning or be input for supervisors related to aspects that still need to be developed. As a whole the supervision of learning in the 4.0 era learning model lesson study to improve the professionalism of teachers in the fostered areas after mentoring showed an increase in meeting the standards of the process and quality of English learning in general. Increased acquisition of the results of the supervision of learning era 4.0 model lesson study in the two target schools above can provide a picture that can improve the professionalism of teachers and supervisor supervisors very significantly.